Documenting The Richness of Indonesia Through The Cultural Color of Sumatera’s Traditional Textile and Culinary Product - Mita Purbasari; Anita Rahardja (Humaniora, 2016)
Analysis of cultural color was an approach to a better understanding color from cultural stand point, unlike the others color studies which looked at the psychological aspect of color. Johannes Itten’s theory of color served as a thinking base in this study. The theory was reflected in the cultures of Indonesia and represented by island of Sumatera (Aceh Darussalam, Medan, Padang, Bengkulu, Palembang, and Lampung). The scope of the subject matters was limited to traditional textile products such as traditional costumes, bridal apparel, and culinary. The textile products were chosen because they became reflection of a culture whose place was close to society and this color became the its own identity. The research method was qualitative that consisted of doing literature study, interviewing experts (historians and artists), and visiting cultural centers especially the ones associated with textile and culinary product. The result of this study is presented in the form of morphological matrix on cultural color. The matrix of analysis is supported with arguments and a classroom experiment, which allows students to use, cultivate, and maximize the method of applying color in visual communication to achieve harmony and contrast.